Integration of Islamic Law and Positive Law in the Context of Legal Pluralism in Indonesia - Hamdan Arief Hanif; Indah Listyorini (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
In Indonesia, the coexistence of multiple legal systems namely the national or positive law, customary (adat) law, and Islamic law (sharia/fiqh) gives rise to complex challenges of harmonisation within a plural legal order. This article examines how Islamic law and positive law are integrated (or fail to integrate) in the Indonesian legal system, especially in light of the country’s foundational ideology of Pancasila and plural religious and cultural composition. Using a normative‐juridical approach complemented by doctrinal analysis of legislation, judicial decisions and scholarly literature, this research explores the structural, normative and practical dynamics of integration, the obstacles encountered (such as conflicting norms, jurisdictional overlaps, human-rights tensions), and the opportunities for re-conceptualising legal pluralism as complementary rather than competing systems. The results indicate that while Islamic law is not fully codified as national law, its values have increasingly been absorbed into positive law through mechanisms such as legislative receptio, judicial interpretation, and regional regulation (particularly in special-autonomy regions). The discussion highlights that sustainable integration depends on recognition of pluralism, legal certainty, rights protection, and contextualisation of Islamic legal norms within national and global human-rights frameworks. The conclusion proposes a model of harmonised pluralism that respects diversity while maintaining coherence and justice in the national legal order.